2014
DOI: 10.1021/jp411209n
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the 248 nm Photolysis Products of HCNO (Fulminic Acid)

Abstract: IR diode laser spectroscopy was used to detect the products of HCNO (fulminic acid) photolysis at 248 nm. Five product channels are energetically possible at this photolysis wavelength: O + HCN, H + (NCO), CN + OH, CO + NH, and HNCO. In some experiments, isotopically labeled (18)O2, (15)N(18)O and C2D6 reagents were included into the photolysis mixture in order to suppress and/or isotopically label possible secondary reactions. HCN, OC(18)O, C(18)O, NCO, DCN, and NH molecules were detected upon laser photolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Many secondary reactions following the photolysis can therefore occur. Most but not all of this secondary chemistry is identical to that considered in our previous study [8]:…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Many secondary reactions following the photolysis can therefore occur. Most but not all of this secondary chemistry is identical to that considered in our previous study [8]:…”
Section: Resultssupporting
confidence: 67%
“…3) × 10 -11 cm 3 molecule -1 s -1 and k 6 ≤ 2.1 × 10 -13 cm 3 molecule -1 s -1 at 298 K. While the rate of H + HCNO, reaction (7), is not 6 experimentally known, our previous study [8] showed that it was too slow to affect the results of HCNO photolysis experiments. Reactions (2)-(5) are fast and may produce some of the same product molecules as those probed in these experiments, potentially complicating the interpretation of product yields.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations